Global Warming and Biodiversity Conservation Adaptation Technique in Khageri Watershed, Chitwan - Regmi, Prakash (Bharatpur Pragya: Journal of Multidisciplinary Studies, 2024)
This paper analyzes the land use and land suitability analysis of Khageri watershed in Chitwan. Nepal has been experienced water scarcity in dry season and flood inundation in monsoon. Khageri watershed is the source of water for west Chitwan irrigation and it also this area is rich biodiversity area. This area covered 67.2 percent of jungle in 2024 and that was 74.5 percent in 1999. The study utilized secondary map data sources like Google Earth Pro, USGS, FAO, and ARCMAP 10.8., and eight parameters were used to analyze land suitability analysis. There were 219 small locations found suitable for water harvest areas. Out of which, ten majors’ locations have been chosen and further analysis with 5-meter earth dams assumed and they were extended. The extended ten locations cover 712 hectors of land, and they can harvest 24,760,930 cubic meters of water.